Ethnobotanical review of wild edible plants of Nepal - Gautam, Ratna Silwal; Shrestha, Sudha Joshi; Shrestha, Ila (Journal of Natural History Museum, 2022)
Wild edible plants refer to edible species that are not cultivated or domesticated for use. Different parts of wild plants collected from natural habitats are consumed as food in varied forms in different parts of Nepal. The main objective of this study was to review the wild edible plant species of Nepal. It compiled 436wild edible plant species from 110 families and 277 genera. Among them 208 (48%) species were herbs, 68 (16%) species shrubs, 120 (27%) species trees and 40 (9%) species were climbers. The study showed that 95 % of wild edible plant species were angiosperm, 5 % were pteridophytes and very negligible percentage (only one species) was gymnosperm. Fabaceae was the family with the highest number (27 sps.) followed by Moraceae and Rosaceae (24 sps.) and Polygonaceae and Asteraceae (19 sps.) of wild edible plants. Maximum numbers of plant species (208 sps.) were consumed as vegetables and the mostly used part of was found as the fruits (168 sps.) followed by leaves (93 sps.), shoots (52 sps.) and flowers (20 sps.).